KAAYA: A Wearable AAC Device for Enhancing Daily Communication of Learners with Mild Intellectual Disabilities - Mosvita, Divannia Shayna Rahmaellery Putri; Maharani, Guchy Falya; Homdijah, Oom Sitti; Akhlan, Riksma Nurahmi Rinalti (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study developed and evaluated KAAYA, a low-tech wearable augmentative and alternative communication device to improve functional and expressive communication in a child with mild intellectual disability. A mixed methods design integrated quantitative and qualitative data. One eight-year-old participant with adequate receptive language but limited expressive skills received the intervention. Data sources included structured classroom observations, a receptive and expressive communication rubric, pretest and posttest assessments, and interviews with teachers and parents. The pretest total score was nine, indicating reliance on nonverbal gestures and difficulty expressing basic needs. After three weeks, the posttest rose to twenty-four,24, and the child used KAAYA buttons to request food, toileting, and play. Session-by-session observations and PND indicated progressive gains during intervention. Qualitative data showed reduced miscommunication, greater independence, and improved social participation at school and home. Results suggest that KAAYA is an effective, practical, and context-appropriate low-tech wearable AAC device for supporting functional communication and social participation in children with mild intellectual disabilities across structured educational settings and daily routines.